Genetic variation may play a crucial role in non-coding RNA biogenesis - Kandhavelu, Jeyalakshmi; Kandhavelu, Meenakshisundaram (Scientific Research Publishing, 2012)
Transcription, post-transcriptional modification, translation, post-translational modification, DNA replication, and signaling interaction of intra- and extra- cellular components are the relevant mechanisms in gene regulation. Transcription is one of the most important mechanisms in the control of gene expression. Further, post-transcriptional modifications play a crucial role after transcription which determine whether the transcribed gene is coding or non-coding RNA (ncRNAs). Genome-wide analysis of RNAs provides information about the coding RNAs, whereas the status of ncRNAs are still at large and must be discussed in detail as variations in the ncRNAs can lead to different phenotypes. In this short article, we discuss the role of genetic variation in ncRNA genes and how this variation may play a crucial role in ncRNA biogenesis that eventually leads to phenotypic variation and thus speciation.
Keywords: Genome Wide Analysis; Bioinformatics; Genetic Variation; Non-Coding RNA Biogenesis; RNA Structure; Speciation